2019
DOI: 10.15405/epsbs.2019.09.9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Motivation And Stress Levels Toward Happiness Among Adolescents: A Predictor Model

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(59 reference statements)
2
0
0
Order By: Relevance
“…Consistent with previous studies, the study revealed that intrinsic motivation has a significant and positive relationship with happiness. This result is in line with other studies conducted by Ying, Mohamad, Wen, & Ann (2019); Sofiah, Jain, and Fauziah (2013); and Amir and Khoshnam (2018). Academic performance, perceived learning, and personal satisfaction are all factors that contribute to students' success in the context of intrinsic motivation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies, the study revealed that intrinsic motivation has a significant and positive relationship with happiness. This result is in line with other studies conducted by Ying, Mohamad, Wen, & Ann (2019); Sofiah, Jain, and Fauziah (2013); and Amir and Khoshnam (2018). Academic performance, perceived learning, and personal satisfaction are all factors that contribute to students' success in the context of intrinsic motivation.…”
Section: Discussionsupporting
confidence: 93%
“…Happiness and intrinsic motivation are significantly positively correlated. The study's findings demonstrate that intrinsic characteristics strongly affect happiness (Ying, Mohamad, Wen, & Ann, 2019). The research of Sofiah, Jain, and Fauziah (2013), which outlined the existence of a link between intrinsic motivation and happiness, supports this.…”
Section: Intrinsic Motivationsupporting
confidence: 52%